2013
DOI: 10.14581/jer.13012
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide Decreases Current-Source Density of High Beta Frequency of Electroencephalogram

Abstract: Background and Purpose:The purpose of this study was to investigate changes in brain current-source density (CSD) of the high frequency band (22–30 Hz) induced by zonisamide (ZNS) in patients with newly diagnosed epilepsy and to correlate with the cognitive performances.Methods:We conducted a 24-week, open-labeled, prospective study in 19 patients. Eelectroencephalography (EEG) and neuropsychological tests (NPs) were conducted at baseline and 24 weeks after starting the medication. Six patients were excluded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As described for TPM, zonisamide also exhibits a sulpha moiety and weak carbon anhydrase inhibition properties, estimated as 100-1000 times lower than acetazolamide (Leppik, 2004). A recent electroencephalography (EEG) study on individuals taking zonisamide for recent-onset epilepsy reported reduced current source density of beta frequencies for areas implicated in language and working memory, such as inferior and middle frontal cortices, anterior cingulate gyri and inferior parietal lobules (Kwon and Park, 2013). In a retrospective analysis of verbal fluency fMRI, comparing patients taking Topiramate (n=32), Zonisamide (51) and Levetiracetam (62) (Wandschneider et al, 2017), we observed a similar influence of zonisamide and TPM on fronto-parietal cognitive networks in patients with focal epilepsy, as measured by verbal fluency fMRI.…”
Section: Topiramate and Zonisamidementioning
confidence: 99%
“…As described for TPM, zonisamide also exhibits a sulpha moiety and weak carbon anhydrase inhibition properties, estimated as 100-1000 times lower than acetazolamide (Leppik, 2004). A recent electroencephalography (EEG) study on individuals taking zonisamide for recent-onset epilepsy reported reduced current source density of beta frequencies for areas implicated in language and working memory, such as inferior and middle frontal cortices, anterior cingulate gyri and inferior parietal lobules (Kwon and Park, 2013). In a retrospective analysis of verbal fluency fMRI, comparing patients taking Topiramate (n=32), Zonisamide (51) and Levetiracetam (62) (Wandschneider et al, 2017), we observed a similar influence of zonisamide and TPM on fronto-parietal cognitive networks in patients with focal epilepsy, as measured by verbal fluency fMRI.…”
Section: Topiramate and Zonisamidementioning
confidence: 99%
“…Only one study investigated potential pathomechanisms of cognitive impairment due to ZNS, describing decreased current-source density of high beta frequency in regions relevant to language and working memory during a verbal fluency task. 9 All of the above studies are hampered by small sample sizes.…”
mentioning
confidence: 99%
“…Some AEDs resulted in dysfunction of these regions when cognitive tasks were given. Executive dysfunction with topiramate (TPM) or zonisamide (ZNS) was demonstrated by functional MRI (fMRI) and current-source density of electroencephalogram (EEG) [38,39]. Because TPM and ZNS have multiple modes of action including GABAergic activity, we suggest any AED affecting these regions can cause apathy as well as cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%